VALIDITAS IDMIGRAINETM VERSI INDONESIA SEBAGAI ALAT SKRINING MIGRAIN PADA PELAJAR SMU 6 BANDUNG - Yusmahenry Galindra, Yusuf Wibisono, Thamrin Syamsudin (NEURONA, 2014)
INTRODUCTION THE INCREASING PREVALENCE OF MIGRAINE IN SCHOOLAGE CHILDREN RESULTED IN THE DECREASE OF LIVE QUALITY AND THE NORMAL DAILY ACTIVITY FOR THAT REASON IT IS IMPERATIVE TO DIAGNOSE MIGRAINE ACCURATELY IN A HUGE POPULATION THEREFORE AN EFFECTIVE AND EFFICIENT SCREENING TOOL IS NEEDED THE IDMIGRAINETM IS A SCREENING TOOL WHICH HAS A PROVEN VALIDITY WIDELY USED IN MANY COUNTRIES AND TRANSLATED IN MANY LANGUAGE HOWEVER THE INDONESIAN TRANSLATION HAS NEVER BEEN USED